2017
DOI: 10.1007/s00213-017-4719-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of intracellular Ca2+ signaling in the antinociceptive and discriminative stimulus effects of the imidazoline I2 receptor agonist 2-BFI in rats

Abstract: Rationale Recent research has established the imidazoline I2 receptor as a promising target for the development of novel analgesics. However, despite an increasing understanding of imidazoline I2 receptor-mediated behavioral effects, little is known about post-I2-receptor signaling mechanisms. Objective This study examined the effects of several inhibitors of Ca2+ signaling mechanisms on two behavioral effects of the prototypical imidazoline I2 receptor ligand 2-BFI. Methods The von Frey filament test was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…These results support previous findings regarding dissociation between I 2 receptor-mediated behavioural effects (Siemian et al, 2017) and provide further in vivo evidence that I 2 receptor populations and/or post-receptor signalling mechanisms are heterogeneous. In contrast, the hypothermic and discriminative stimulus effects of 2-BFI appear to be mediated by distinct, unrelated mechanisms.…”
Section: Figuresupporting
confidence: 91%
See 4 more Smart Citations
“…These results support previous findings regarding dissociation between I 2 receptor-mediated behavioural effects (Siemian et al, 2017) and provide further in vivo evidence that I 2 receptor populations and/or post-receptor signalling mechanisms are heterogeneous. In contrast, the hypothermic and discriminative stimulus effects of 2-BFI appear to be mediated by distinct, unrelated mechanisms.…”
Section: Figuresupporting
confidence: 91%
“…We finally tested the role of monoaminergic mechanisms in mediating the discriminative stimulus effects of 2-BFI. Support for this also comes from a recent finding that the 5-HT 2A receptor agonist DOM did not substitute for 2-BFI (Siemian et al, 2017). Interestingly, MacInnes and Handley (2002; reported that serotonergic and noradrenergic components were involved in the discriminative stimulus effects of 2-BFI.…”
Section: Figurementioning
confidence: 96%
See 3 more Smart Citations